METHODS FOR TEACHING SPEAKING SKILL AT THAMAR SCHOOLS AND THEIR IMPACTS ON LEARNERS’ ORAL COMPETENCY - Jameel Ahmed Alghaberi (University of Kuningan, 2019)
In the Republic of Yemen, English is taught as a foreign language (FL) in schools and universities. It is a compulsory subject in the curriculum of Yemeni schools and universities and it is the only foreign language that is taught in all Yemeni Public Schools. However, teachers and educators complain about students’ lack of oral competency. Hence, this paper attempts to evaluate the current teaching methods, approaches, techniques and activities used for teaching English speaking skill at Thamar Secondary Public Schools. Besides, it also investigates the utilization of instructional aides as well as technological resources and facilities available at schools in Thamar city. Three different data collection techniques were used, namely observation, questionnaire, and interview. The results revealed that English teachers in Thamar still follow the traditional teaching methods. Above all, speaking skill is almost neglected. The lack of proper teaching methods and activities coupled with the absence of instructional aides stand behind students’ deficiency in English speaking. Thus, it is recommended that several training sessions for in-service teachers to be held in order to familiarize them with the methods, techniques, and activities used for teaching English speaking skill.